Contemporary Issues in International Business Institutions, Strategy and Performance (The Academy of International Business, 2018)
The ACADEMY OF INTERNATIONAL BUSINESS (UK and Ireland Chapter) Published in association with the UK and Ireland Chapter of the Academy of International Business. This brand new edited collection addresses the growing uncertainty and socio-economic challenges of globalisation and its profound implications for the strategies and operations of multinational enterprises (MNEs). Responding to the new balance in international business, the authors offer valuable insights into the co-evolutionary processes involved in headquarters-subsidiary relationships, the need for novel strategies by MNEs to retain competitive advantage, improve performance and contribute to the global economy.